A review on extracorporeal membrane oxygenation and kidney injury. Issue 3 (16th December 2020) - Gu, Ming; Mei, Xiang‐Lin; Zhao, Ya‐Nan
Abstract: Extracorporeal membrane oxygenation (ECMO) is inevitable external life support in case of cardiac and respiratory failure since the 1970s. Acute kidney injury (AKI) and the requirement of renal replacement therapy (RRT) is a potential risk among these patients. This review aims to give an overview of the risk of AKI, RRT, and associated mortality among the patients who received ECMO for any of its indications. PubMed database was searched to find the relevant literature and the reference list of included studies was also searched for additional studies. The incidence of AKI ranged from 30% to 78% and RRT from 47% to 60% in ECMO patients. The pathophysiology of AKI in ECMO is multifactorial, and includes ischaemia, RBCs breakdown, comorbidity, conversion of zymogen form of pro‐inflammatory mediators, structural alteration of the kidney, coadministration of nephrotoxic drugs, coagulation abnormality, and oxidative stress. ECMO was associated with the higher incidence of renal abnormalities, AKI, requirement of RRT, and associated mortality. Patients who underwent RRT had improved renal function and reduced overall mortality compared to the non‐RRT group among the ECMO patients. Currently, there is no consensus evidence to support the superior use of the inline hemofilter system over continuous renal replacement therapy among patients who had AKI during ECMO.